Religion, Radicalization, and Violent Extremism? - Droogan, Julian (Does religion cause violence?, 2018)
The question of how far religion can be considered a central factor for the inspiration of terrorism has been a topic of heated debate by academics and policymakers since the al-Qa‘ida (AQ) attacks of September 11, 2001, and, indeed, since before them. The subsequent “franchising” of AQ operations across much of North Africa, the Middle East, and Asia; its emergence as an internationalized terrorist brand espousing the goals of radical Islamist revolution and militant jihad; and the later evolution of one of these subsidiaries, AQ in Iraq, to become an independent and apocalyptically inspired insurgency under the name Islamic State of Iraq and Syria, or simply “Islamic State” (IS), has further focused attention to the question of the exact relationship between religion and violent extremism. More recently, attempts by both AQ and IS to remotely inspire and equip individuals with the extremist ideology and practical tactics of terrorism, and to empower these individuals to conduct acts of violence locally, have led to a series of lone-individual attacks across the world and shifted focus to questions of “radicalization” to violent extremism. Just what role religion plays in this supposed process of radicalization to violent extremism, and, indeed, whether “radicalization” is an appropriate concept for explaining the inspiration of the lone self-empowered actor, have become two of the most significant and debated questions in terrorism studies and counterterrorism policy formation....